Capillary Flow Rates in the Duodenum of Pediatric Ulcerative Colitis Patients Are Increased and Unrelated to Inflammation. Issue 3 (September 2017) - Zaidi, Deenaz; Churchill, Lucas; Huynh, Hien Q.; Carroll, Matthew W.; Persad, Rabin; Wine, Eytan
ABSTRACT: Background and Aim: Inflammatory bowel diseases (IBD), including Crohn disease (CD) and ulcerative colitis (UC), are chronic pediatric disorders. Changes in vasculature are described in IBD, but these could be secondary to inflammation and the role in pathogenesis is poorly understood. Assessing circulatory changes in typically unaffected sites in IBD (eg, duodenum), when inflammation is absent, can identify vascular changes associated with pathogenesis. The aim of the study is to measure capillary flow rates in duodenal mucosa using probe-based confocal laser endomicroscopy (pCLE) during endoscopy in children with IBD. Methods: Images of villi with visible blood vessels obtained using pCLE were captured as video sequences. Capillary flow rate (mm/s) was calculated by dividing the distance travelled by blood cells by the duration of the sequence. Flow rates were correlated with various clinical parameters. Results: Forty-five patients (22 non-IBD, 14 CD, 9 UC) were included in the study. Duodenal capillary flow rates were significantly higher in UC patients (0.75 ± 0.07 mm/s) as compared to non-IBD (0.57 ± 0.03) and CD (0.65 ± 0.04). There was no correlation between serum hemoglobin and albumin, disease activity indices, serum inflammatory markers, and capillary flow rates in patients. Conclusions: This pilot study shows, for the first time, increased capillary blood flow in the duodenum of UC patients that was unrelated to inflammatory markers or disease activity. Thus, early vascular changes can be assessed using pCLE during endoscopy. Abstract : Supplemental Digital Content is available in the text